KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS PELAYANAN PUBLIK DI KANTOR DESA MADDENRA KECAMATAN KULO KABUPATEN SIDENRENG RAPPANG - Fitri Handayani; Erfina Erfina; Pratiwi Ramlan (PRAJA: Jurnal Ilmiah Pemerintahan, 2020)
Competence of human resources on the quality of public services in the Maddenra Village Office, Kulo District, Sidenreng Rappang Regency and to determine the factors that influence human resource competence in the Maddenra Village Office, Kulo District, Sidenreng Rappang Regency. The population of this study was 2,095 people. Samples were 95 people. The sampling technique used is Purpossive Sampling. This type of research is quantitative descriptive. Data collection techniques used were observation, interviews, questionnaires and literature study. The data analysis technique used is descriptive statistics and with the help of SPSS application version 21. The results showed that the Human Resources Competence at the Maddenra Village Office with a percentage of 58.16% was in the unfavorable category. The quality of public services at the Maddenra Village Office with a percentage of 58.30% is in the poor category. Based on the value of t count> t table or 9,855> 1,989, then H0 is rejected, it means that Human Resources Competence has a significant effect on the Quality of Public Services in the Maddenra Village Office, Kulo District, Sidenreng Rappang Regency with a percentage contribution of 51.1% influence. Factors that Influence Human Resources Competence: a. Internal factors: 1) Employees in improving service capability 58%. 2) The ability of employees to anticipate public complaints 59%. 3) Increased employee use of computers 56%. b. External factors: 1) Government attitudes towards human resource support 59%. 2) Community involvement in improving services 57%. 3) employee training to support technology development 51%. Based on the description above, it can be concluded that the factors that influence the Competency of Human Resources in the Office of Maddenra Village with a percentage of 56.67% are in the unfavorable category.